Natural selection in human populations. - D.F. Roberts and; G. A.Harrison (Pergamon Press, 1959)
"For the first full meeting of the newly formed Society for the Study of Human Biology, it seemed appropriate to address that biological field in which the most notable recent progress has been made: human genetics. Since the meeting was held in 1958, the centenary of the publication of Darwin-Wallace's work, it seemed particularly appropriate to choose natural selection as the topic. Accordingly, a symposium entitled "Natural Selection in Man" was held in the Anatomy Theater of University College London on November 8, 1958". (Copiado del prefacio).